2016
DOI: 10.1111/jcal.12159
|View full text |Cite
|
Sign up to set email alerts
|

Using robot animation to promote gestural skills in children with autism spectrum disorders

Abstract: School-aged children with autism spectrum disorders (ASDs) have delayed gestural development, in comparison with age-matched typically developing children. In this study, an intervention program taught children with low-functioning ASD gestural comprehension and production using video modelling (VM) by a computer-generated robot animation. Six to 12-year-old children with ASD (N = 20; IQ < 70) were taught to recognize 20 gestures produced by the robot animation (phase I), to imitate these gestures (phase II) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…Children on the spectrum lack the ability to properly communicate their needs [64,103]. Generalization of skills is usually done with other children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children on the spectrum lack the ability to properly communicate their needs [64,103]. Generalization of skills is usually done with other children.…”
Section: Resultsmentioning
confidence: 99%
“…Children were found to be more intrigued to interact with robots as compared to humans due to the limited complexity of robots [16]. There have been many reported evidence of the efficacy of using robots for ASD intervention [16,98,103]. Many studies have demonstrated that robots can be used to elicit many behaviors, such as imitation, joint attention, eye contact, and gestural responses [19][20][21]47,113].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to convey emotions, exhibiting different personalities, employing communication cues, and forming social relationships are some of the traits that make social robots different from typical toys [8][9] [10]. Introducing a new stimuli (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have employed humanoid robots for treatment plans for children with ASD [66][67][68][69][70][71][72][73][74][75][76][77][78][79]. However, some research has used non-humanoid robots [11,[80][81][82][83][84].…”
Section: Social Robotsmentioning
confidence: 99%